Revalidación de Liolaemus choique Abdala, Quinteros, Scrocchi y Stazzonelli, 2010 (Iguania: Liolaemidae) - Ruiz, Maria Soledad (2019)
The description of Liolaemus choique was based on an exhaustive morphological diagnosis. However, a posterior phylogeographic study suggested that it would be a junior synonym of L. smaug. Herein, we present morphological behavioral and distributional data indicating that L. choique would be considered as a valid species. Therefore, we suggest to revalidate L. choique, as a distinct taxon from L. smaug